2020
DOI: 10.14740/jnr564
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Hyperparathyroidism and Ischemic Stroke Subtypes

Abstract: Background: Up to date, a substantial amount of research has remarked on the potential role of parathormone (PTH) in the development of subclinical and clinical vascular diseases. However, the association between the hyperparathyroidism and cerebrovascular disease has rather been underestimated in the literature. Herein, we aimed to investigate the association between serum PTH levels and ischemic stroke.Methods: Serum PTH levels were measured in all patients with ischemic stroke who were hospitalized in the Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Several studies were focussing on the association between PTH and stroke and clarified a significant correlation between HPT and ischaemic stroke. However, these studies were done among nonrenal failure patients [39][40][41] Our study revealed that; SBL in conventional MRI imaging were highly positive correlated with serum calcium (cut off point ˃7.5 mg/ dL), duration of haemodialysis (cut off point ˃2 years) and PTH (cut off point ˃585 pg/mL) on ROC curve analysis and multivariate analysis. Therefore, PTH and the duration of dialysis may be considered as independent predictor factors for the presence of SNL and strongly correlated to it, which may be because of combined cerebral small A recent study by Honglan et al showed that ESRD patients who had HPT were associated with cognitive and cerebral dysfunction 42 and a study in Japan done by Tagawa et al found that haemorrhagic stroke was associated with PTH level >500 pg/mL, and ischaemic stroke was not related to PTH level.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies were focussing on the association between PTH and stroke and clarified a significant correlation between HPT and ischaemic stroke. However, these studies were done among nonrenal failure patients [39][40][41] Our study revealed that; SBL in conventional MRI imaging were highly positive correlated with serum calcium (cut off point ˃7.5 mg/ dL), duration of haemodialysis (cut off point ˃2 years) and PTH (cut off point ˃585 pg/mL) on ROC curve analysis and multivariate analysis. Therefore, PTH and the duration of dialysis may be considered as independent predictor factors for the presence of SNL and strongly correlated to it, which may be because of combined cerebral small A recent study by Honglan et al showed that ESRD patients who had HPT were associated with cognitive and cerebral dysfunction 42 and a study in Japan done by Tagawa et al found that haemorrhagic stroke was associated with PTH level >500 pg/mL, and ischaemic stroke was not related to PTH level.…”
Section: Discussionmentioning
confidence: 75%
“…Onder and Arslan [30] studied 158 patients with ischemic stroke and found that 31 of the patients (19.6%) had high serum parathyroid hormone levels. In a 1972 study, Boström et al investigated the incidence of stroke in hyperparathyroid patients ( n = 170), which was found to be 7.1% [69].…”
Section: Hyperparathyroidismmentioning
confidence: 99%